Answer:
Pythagorean Theorem: a² + b² = c²
Step-by-step explanation:
7-24-25
7² + 24² = 25²
49 + 576 = 625
625 = 625
9-40-41
9² + 40² = 41²
81 + 1600 = 1681
1681 = 1681
If you would like to solve the equation 3 * (3 * x - 1) + 2 * (3 - x) = 0, you can calculate this using the following steps:
3 * (3 * x - 1) + 2 * (3 - x) = 0
3 * 3 * x - 3 * 1 + 2 * 3 - 2 * x = 0
9 * x - 3 + 6 - 2 * x = 0
7 * x + 3 = 0
7 * x = - 3 /7
x = - 3/7
The correct result would be - 3/7.
Answer:
Step-by-step explanation:
Dimensions: 1 x 1 x 36 or 12 x 3 x 1 or 9 x 4 x 1 or 9 x 2 x 2